Effectiveness of the AJCC 8th edition staging system for selecting patients with T1–2N1 breast cancer for post-mastectomy radiotherapy: a joint analysis of 1986 patients from two institutions - Shulian Wang; Ge Wen; Yu Tang; Yong Yang; Hao Jing; Jianyang Wang; Jianghu Zhang; Xuran Zhao; Guangyi Sun; Jing Jin; Yongwen Song; Yueping Liu; et al. (BMC Cancer, 2020)
Abstract Background The role of post-mastectomy radiotherapy (PMRT) in the treatment of patients with T1–2N1 breast cancer is controversial. This study’s purpose was to evaluate the risk of recurrence of T1–2N1 breast cancer and the efficacy of PMRT in low-, medium- and high-risk groups of patients. Methods Post-mastectomy patients with T1–2N1 breast cancer were restaged according to the American Joint Committee on Cancer Staging Manual, 8th edition (AJCC 8th ed.) staging system. Recurrence scores were generated using prognostic factors identified for loco-regional recurrence and distant metastasis in patients without PMRT, and three risk groups were identified. Rates of loco-regional recurrence and distant metastasis were calculated with a competing risk model and compared using Gray’s test. Disease-free survival and overall survival were calculated using the Kaplan-Meier method and compared using the log-rank test. The Cox proportional hazards regression model was used for the multivariate analysis. Results Data from 1986 patients (1521without PMRT; 465 with PMRT) were analyzed. Patients without PMRT were stratified into low-, intermediate- and high-risk groups by age, tumor location, AJCC 8th ed. stage, number of positive nodes and lympho-vascular invasion. The 5-year loco-regional recurrence rate and distant metastasis rates for the three risk groups were significant at 2.5, 5.4 and 16.2% (p <  0.001) respectively, and 4.9, 8.4 and 18.6% (p <  0.001) respectively. In the high-risk group, loco-regional recurrence (p <  0.001), and distant metastasis (p = 0.044) were significantly reduced, and disease free survival (p = 0.004), and overall survival (p = 0.029) were significantly improved after PMRT. In the low- and intermediate-risk groups, PMRT had no significant effect on loco-regional recurrence (p = 0.268), distant metastasis (p = 0.252), disease free survival (p = 0.608) or overall survival (p = 0.986). Conclusion Our results showed no benefits of PMRT in the low-risk group, and thus, omitting PMRT radiotherapy in this population could be considered.